Aerosol is the optimal route of respiratory tract infection to induce pathological lesions of colibacillosis by a lux-tagged avian pathogenic Escherichia coli in chickens. Issue 5 (3rd September 2021) - Paudel, Surya; Fink, Dieter; Abdelhamid, Mohamed Kamal; Zöggeler, Anna; Liebhart, Dieter; Hess, Michael; Hess, Claudia
ABSTRACT: Pathogenesis of colibacillosis caused by avian pathogenic Escherichia coli (APEC) in poultry is unclear and experimental studies reveal substantial inconsistency. In this study, the impact of three infection routes differing in the site of deposition of inoculum in the respiratory tract, were investigated. Two-weeks-old chickens were infected with a lux -tagged APEC strain via aerosol, intranasally or intratracheally, and sequentially sampled along with uninfected birds. At 1 and 3 days post infection (dpi), liver or spleen to body-weight ratios in all infected groups were significantly higher than in negative control, while at 7 dpi, such differences were significant in both organs in the aerosol-infected group. The infection-strain colonized tracheas and lungs in infected birds at 1 dpi and persisted until 7 dpi. Among infected groups, in lungs, bacterial load at 1 dpi was significantly lower in intranasally-inoculated birds. Histology revealed that, independent of infection route, lesions were mostly seen in the lower respiratory organs (lungs and air sacs) characterized by bronchitis/pneumonia and airsacculitis. Birds infected via aerosol showed the highest mean lesion score in lungs while intranasal application caused the mildest pathological changes, and difference between the two groups was significant at 1 dpi. In spleen, heterophilic infiltrations were prominent in affected birds. Interestingly, tracheas were pathologically unaffected. Altogether, the results demonstrated the importance of infection route, with aerosol being the most suitable to induce pathological lesions of colibacillosis without predisposing factors. Furthermore, the lux -tagged APEC strain was discriminated from native isolates enabling exact differentiation and enumeration. RESEARCH HIGHLIGHTS Lux -tagged APEC strain was used for infection to differentiate from native E. coli . Pathologically, lungs, air sacs and spleen but not trachea were affected. The route of infection strongly impacts the pathological outcome with APEC. The infection with APEC via aerosol caused the most severe lesions in chickens.